Listeria Meningitis and Nontyphi Salmonella Bloodstream Infection in an Infant - Immergluck, Lilly C.; Chan, Trisha; Meyer, Rebecca; Khizer, Saadia; Ngyuen, Van (Journal of Pediatric Infectious Diseases, 2015)
To describe a case of an infant with both listeria meningitis and nontyphi Salmonella bacteremia and compare incidence of these two foodborne pathogens in Atlanta, Georgia, United States from 2000 to 2009. An infant presented with two foodborne pathogens without an identifiable source. There are no previous reports of coinfection with L. monocytogenes and nontyphi Salmonella. L. monocytogenes and nontyphi Salmonella remain important foodborne pathogens and source of infection for this age group.
Keywords: listeria monocytogenes; nontyphi Salmonella; infant